Design and Fabrication of Photo-Responsive Hydrogel for the Application of Functional Contact Lens - Lin, Xiaoxia; Zhang, Haitao; Qin, Yuqing; Hu, Xiaohong (Frontiers in Materials, 2021)
Traditional hydrogel has usually had restricted application in the biomedical field due to lack of a control unit. Herein, Azobenzene (AZO), as a typical kind of photo-response molecule, was introduced into hydrogel by polymerization to provide a control unit for hydrogel. Simultaneously, the immobilization of AZO end group would solve the problems of uncontrollable recovery and light fatigue for AZO small molecules according to previous research. In the research, two kinds of crosslinkable AZO molecules, namely AZO crosslinker and AZO monomer, were synthesized as functional monomers or crosslinkers. Further, AZO copolymerized hydrogel and AZO crosslinked hydrogel were obtained. In order to estimate fundamental properties for contact lenses, gelation time and swelling ratio of hydrogels as a function of AZO concentration as well as crosslinking type were investigated. Moreover, synthesized hydrogels exhibited typical porous morphology, but their size and homogeneity were dependent on the type of hydrogel. In order to evaluate photo-responsive performance, detailed photo induced isomerization of both AZO copolymerized hydrogel and crosslinked hydrogel were tracked by UV spectra. The results confirmed the reversible, stable, and controllable photo responsive process. In vitro evaluation was used to investigate drug release behavior using orfloxacin and puerarin as model drugs. It was found that AZO addition as well as hydrogel type would influence puerarin release, but would have little effect on the orfloxacin release behavior in hydrogels. Furthermore, the isomer type in the hydrogel would have some effects on drug release behavior including orfloxacin and puerarin.